A two-ward acute care hospital outbreak of SARS-CoV-2 delta variant including a point-source outbreak associated with the use of a mobile vital signs cart and sub-optimal doffing of personal protective equipment. (January 2023) - O'Grady, H.M.; Harrison, R.; Snedeker, K.; Trufen, L.; Yue, P.; Ward, L.; Fifen, A.; Jamieson, P.; Weiss, A.; Coulthard, J.; Lynch, T.; Croxen, M.A.; et al.
Summary: Background: The arrival of the Delta variant of SARS-CoV-2 was associated with increased transmissibility and illness of greater severity. Reports of nosocomial outbreaks of Delta variant COVID-19 in acute care hospitals have been described but control measures varied widely. Aim: Epidemiological investigation of a linked two-ward COVID-19 Delta variant outbreak was conducted to elucidate its source, risk factors, and control measures. Methods: Investigations included epidemiologic analysis, detailed case review serial SARS-CoV-2 reverse transcriptase–polymerase chain reaction (RT–PCR) testing of patients and healthcare workers (HCWs), viral culture, environmental swabbing, HCW-unaware personal protective equipment (PPE) audits, ventilation assessments, and the use of whole genome sequencing (WGS). Findings: This linked two-ward outbreak resulted in 17 patient and 12 HCW cases, despite an 83% vaccination rate. In this setting, suboptimal adherence and compliance to PPE protocols, suboptimal hand hygiene, multi-bedded rooms, and a contaminated vital signs cart with potential fomite or spread via the hands of HCWs were identified as significant risk factors for nosocomial COVID-19 infection. Sudden onset of symptoms, within 72 h, was observed in 79% of all Ward 2 patients, and 93% of all cases (patients and HCWs) on Ward 2 occurred within one incubation period, consistent with a point-source outbreak. RT–PCR assays showed low cycle threshold ( C T ) values, indicating high viral load from environmental swabs including the vital signs cart. WGS results with ≤3 SNP differences between specimens were observed. Conclusion: Outbreaks on both wards settled rapidly, within 3 weeks, using a `back-to-basics' approach without extraordinary measures or changes to standard PPE requirements. Strict adherence to recommended PPE, hand hygiene, education, co-operation from HCWs, including testing and interviews, and additional measures such as limiting movement of patients and staff temporarily were all deemed to have contributed to prompt resolution of the outbreak.